Cultivo de milho sob sistema de manejo e culturas antecedentes nos tabuleiros costeiros - Ferreira, Olavo José Marques (2015)
This study aimed to investigate the influence of different soil management and plant antecedents in the production of green corn cobs, a Yellow Ultisol in the Coastal Plains region in the municipality of São Cristóvão / SE. Soil management systems were used: conventional tillage (CT - use of two plowing and disking), minimum tillage (MT - use of two harrowing) and no-tillage (NT - Desiccation). These systems were chosen to compare the relationship between production and mobilization of the soil. The antecedent plants producing corn were: pigeon pea (Cajanus cajan L. Millsp), hemp (Crotalaria juncea L.), sunflower (Helianthus annuus L.) and millet (Pennisetum glaucum L.). These plants were designed to soil cover, nitrogen fixation, production of organic matter and decompression of the subsurface soil layers by the roots. The harvest of corn aimed to measure the productivity of a regional product easily accepted by consumers and evaluate the best interaction between soil management systems and antecedents plants, with an interesting strategy for local and regional farmers. In the study was made: assessment of the amount and weight of corn cobs in kg.ha-1 and weight of vegetable biomass antecedents plants (kg.ha-1); collecting soil samples in layers 0-10 and 10-20 cm from each plot at management systems for chemical analysis and mechanical penetration resistance (MPR), moisture and bulk density (Bd). The main reason for working with the corn due to the significant technological growth in the state to grow corn. As a result, millet cultivation in minimum tillage, had the highest biomass production reflected a more organic matter in the soil.The corn crop in areas with millet planting in MT and NT had higher production in quantity and weight of ears of corn. Most Bd CT was obtained when performed planting pigeon pea. As for MPR, the highest values were observed in the CT and MT, and the lowest MPR values obtained in NT in layers 10 -15 and 15-20 cm. In NT, planting sunflower allowed smaller MPR values in relation to the sun hemp cultivation. The results suggest that the use of antecedents plants, mainly millet, associated to soil management in No-till systems and Minimum Cultivation can help improve the quality of the soil, from the physical point of view, leading to improved productivity in the corn crop cultivated in the Coastal Plains region.